Obstructive sleep apnea as a modifier of endocrine toxicities associated with immune checkpoint inhibitors in lung cancer - Pisanu, Lucrezia; Tondo, Pasquale; Bertuccio, Francesco; Conio, Valentina; Arminio, Maria; Mucaj, Klodjana; Gallo, Elisabetta; Montini, Simone; Saddi, Jessica; Corallo, Salvatore; Corsico, Angelo G.; Insalaco, Giuseppe; et al. (Frontiers in Immunology, 2026)
Obstructive sleep apnea (OSA) is one of the most common sleep disorders in the general population. It is characterized by recurrent alterations in nocturnal oxygenation, which have wide-ranging consequences on health. Beyond its well-established links to cardiovascular, neurocognitive, and metabolic diseases, recent evidence suggests a possible association between OSA and cancer, particularly lung cancer, one of the leading causes of death worldwide. The advent of immunotherapy has significantly improved outcomes for lung cancer patients in both early and advanced stages. However, immunotherapy is frequently associated with endocrine toxicities, which may overlap or interact with the metabolic alterations observed in OSA. This perspective aims to emphasize the clinical relevance of diagnosing and treating OSA in lung cancer patients undergoing immunotherapy, as proper management could help optimize both therapeutic efficacy and overall health.